2009
DOI: 10.1021/ja805843n
|View full text |Cite
|
Sign up to set email alerts
|

A Hierarchy of Homodesmotic Reactions for Thermochemistry

Abstract: Chemical equations that balance bond types and atom hybridization to different degrees are often used in computational thermochemistry, for example, to increase accuracy when lower levels of theory are employed. We expose the widespread confusion over such classes of equations and demonstrate that the two most widely used definitions of “homodesmotic” reactions are not equivalent. New definitions are introduced and a consistent hierarchy of reaction classes (RC1 – RC5) for hydrocarbons is constructed: isogyric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
543
2
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 557 publications
(562 citation statements)
references
References 158 publications
(300 reference statements)
13
543
2
4
Order By: Relevance
“…Recently, Wheeler, Allen, and co-workers have examined these reaction schemes and defined a hierarchy of essentially convergent fragmentation reactions for closed-shell hydrocarbons. 55 While they suggest a practical scheme for homodesmotic and hyperhomodesmotic radical reactions, there may be many ways of constructing such reactions. Using conventions of closed-shell organic reactions, our predicted "homodesmotic" and "hyperhomodesmotic" ∆ f H 298.15°v alues for cyclohexadienyl differed from those of the isodesmic approaches by up to 17.6 kJ mol -1 !…”
Section: Theoretical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Wheeler, Allen, and co-workers have examined these reaction schemes and defined a hierarchy of essentially convergent fragmentation reactions for closed-shell hydrocarbons. 55 While they suggest a practical scheme for homodesmotic and hyperhomodesmotic radical reactions, there may be many ways of constructing such reactions. Using conventions of closed-shell organic reactions, our predicted "homodesmotic" and "hyperhomodesmotic" ∆ f H 298.15°v alues for cyclohexadienyl differed from those of the isodesmic approaches by up to 17.6 kJ mol -1 !…”
Section: Theoretical Resultsmentioning
confidence: 99%
“…33 Wheeler, Allen, and coauthors have found an average error of 2.5 kJ mol -1 relative to their post-CCSD(T) "focal point" model chemistry values for the BDEs of 1,3-cyclohexadiene and cyclopentadiene using an isodesmic scheme with CCSD(T)/cc-pVTZ computations. 55 Post-CCSD(T) electron correlation effects often cancel and quickly converge to a "full-CI" limit once connected quadruple excitations are incorporated into the wave function. This has been observed for isogyric reaction energies of smaller hydrocarbons, 57 as well as for atomization energies and proton affinities of small molecules.…”
Section: Theoretical Resultsmentioning
confidence: 99%
“…In the case of direct calculations, high level molecular orbital methods (CCSD(T) usually) or density functional methods (DFT) are combined with isogiryc or isodesmic reactions [8] [9].…”
Section: Introductionmentioning
confidence: 99%
“…SCC try to separate inter-and intra-molecular dispersion by a double-damping formula and the inclusion of higher multipole-rank (R −8 , R −10 ) terms. In addition to vdW complexes it has been tested on four thermochemical benchmark sets: a modified version of IDHC77 [64] (the alkane folding reaction of C 30 H 62 is excluded and the dimerization of anthracene is added) and three test sets [65] consisting of isodesmic bond separation reactions (BSR) [66][67][68] of saturated hydrocarbons (corresponding to reaction class two according to the nomenclature of Schleyer and coworkers [69]). The latter three are subdivided into chains (H), rings (R) and cages (C) (for structures see Fig.…”
mentioning
confidence: 99%